Comparison of Low-Density Lipoprotein Cholesterol (LDL-C) Goal Achievement and Lipid-Lowering Therapy in the Patients With Coronary Artery Disease With Different Renal Functions - Zhang, Shuang; Li, Zhi-Fan; Shi, Hui-Wei; Zhang, Wen-Jia; Sui, Yong-Gang; Li, Jian-Jun; Dou, Ke-Fei; Qian, Jie; Wu, Na-Qiong (Frontiers in Cardiovascular Medicine, 2022)
To evaluate the relationship between the renal function and low-density lipoprotein cholesterol(LDL-C) goal achievement and compare the strategy of lipid-lowing therapy(LLT) among the coronary artery disease (CHD) patients with different renal function. Methods In this study, we enrolled 933 CHD patients from September 2020 to June 2021 admitted to Cardiometabolic Center of Fuwai Hospital in Beijing consecutively. There were 808 subjects with eGFR≥60 ml/min/1.73m2 who were divided into Group 1 (G1). 125 patients with eGFR <60ml/min/1.73m2 were divided into Group 2(G2). The rate of LDL-C goal attainment (LDL-C<1.4mmol/L) was significantly lower in G2 when compared with that in G1 (24.00% vs. 35.52%, P=0.02), even though there was no significant difference in the aspect of LLT between the two groups (high intensity LLT: 82.50% vs. 85.60% P=0.40). Notably, in G1 group, the proportion of LDL-C goal achievement increased with the intensity of LLT (23.36% vs. 39.60% vs. 64.52% in the subgroup under low/moderate-intensity LLT, or high-intensity LLT without PCSK9 inhibitor (PCSK9i), or high-intensity LLT with PCSK9i, respectively, P<0.005). In addition, in G2 group, there was a trend that the rate of LDL-C goal achievement was higher in the subgroup under high-intensity LLT (26.60% in the subgroup under high-intensity LLT without PCSK9i, 25.00% in the subgroup under high-intensity LLT with PCSK9i) than that under low/moderate-intensity LLT (15.38%, P=0.49). Importantly, after multiple regression analysis, we found that eGFR＜60 ml/min/1.73m2 (OR 1.81; 95%CI, 1.15–2.87; P=0.01) was independent risk factor to impact LDL-C goal achievement. However, the combination strategy of LLT was protective factor for LDL-C goal achievement independently (statin combined with ezetimibe: OR 0.42; 95%CI 0.30-0.60; P<0.001; statin combined with PCSK9i: OR 0.15; 95%CI 0.07-0.32; P<0.001, respectively). Conclusions Impaired renal function (eGFR＜60 ml/min/1.73m2) was an independent risk factor for LDL-C goal achievement in the CHD patients. High intensity LLT with PCSK9i could improve the rate of LDL-C goal achievement significantly. It should be suggested to increase the proportion of high intensity LLT with PCSK9i for CHD patients, especially those with impaired renal function.